Bringing Cancer Prevention to Schools: Evaluation of a Novel Teaching Toolkit - Ana A. Gomes; Nuno Ribeiro; Pedro Oliveira; Pedro Ribeiro; Nuno T. Marcos (American Journal of Health Promotion, 2026)
Purpose cancer prevention is key to reduce disease burden, but is often dependent on individual behavioral choices, many of which are adopted early on during adolescence. A novel cancer prevention teaching toolkit, designed for this audience and the educational context, was evaluated for its adequacy and impact. Design Three complementary methods were used: a students’ evaluation study, a teachers’ survey, and website metrics analysis. Setting Schools and online. Sample 316 high school students (15-21yo), 79 teachers, and 4007 online users. Measures Students’ knowledge was measured by questionnaire and behavior were measured pre- and post-intervention; teacher and student appreciation was assessed via structured survey; usage was evaluated by survey (teachers) and website analytics. Analysis Descriptive statistics summarized appreciation levels; paired statistical tests evaluated changes in knowledge and behavior; network analysis and descriptive statistics for describing usage patterns. Results The toolkit was primarily used by Biology teachers (89.9%) in classroom settings (83.5%). Both teachers and students reported high levels of appreciation and dissemination. Significant knowledge differences between groups of students were observed 30 days post-intervention ( P < 0.001). Approximately 50% of students adopted healthier behaviors, some for the first time. Conclusion This work boldly underlines the importance of purposedly designing cancer prevention contents for adolescents and the educational context, with important implications for the development of future cancer prevention educational programs and public health promotion initiatives.